A categorisation of policy conflicts in distributed systems and network management. (28th May 2021) - Mitropoulos, Sarandis; Gouglidis, Antonios; Giotsas, Vasileios
Policy conflict detection in distributed systems and network management is a crucial issue that strongly influences the management efficiency. In this paper, after investigating thoroughly the related approaches on management policy conflict categorisation, a new systematic categorisation is proposed that is based on four main perspectives, namely, modality, manageability, interoperability and system specification. Subsequently, an organisational network structure that is managed through policies depicts the high applicability of our approach in policy conflict detection, while implementation examples are also given. Finally, conclusions and future work are discussed.